Motion of an active bent rod with an articulating hinge: exploring mechanical and chemical modes of swimming - Raj, Ritu R.; Ganguly, Arkava; Becker, Cora; Shields, C. Wyatt; Gupta, Ankur (Frontiers in Physics, 2023)
Swimming at the microscale typically involves two modes of motion: mechanical propulsion and propulsion due to field interactions. During mechanical propulsion, particles swim by reconfiguring their geometry. When propelled by field interactions, body forces such as phoretic interactions drive mobility. In this work, we employ slender body theory to explore how a bent rod actuator propels due to mechanical swimming via hinge articulations and chemical swimming via diffusiophoretic interactions with a solute field. Although previous theoretical studies have examined mechanical and chemical modes of swimming in isolation, the simultaneous investigation of both modes has remained unexplored. For mechanical swimming, our calculations, both numerical and analytical, recover Purcell's scallop theorem and show that the bent rod actuator experiences zero net displacement during reciprocal motion. Additionally, we calculate the trajectories traced by a bent rod actuator under a non-reciprocal hinge articulation, revealing that these trajectories are influenced by the amplitude of the hinge articulation, geometric asymmetry, and the angular velocity distribution between the two arms of the bent rod actuator.We provide intuitive explanations for these effects using free body diagrams. Furthermore, we explore the motion induced by simultaneous hinge articulations and self-diffusiophoresis. We observe that hinge articulations can modify the effective phoretic forces and torques acting on the bent rod actuator, either supporting or impeding propulsion. Additionally, during selfdiffusiophoretic propulsion, reciprocal hinge articulations no longer result in zero net displacement.In summary, our findings chart a new direction for designing micron-sized objects that harness both mechanical and chemical modes of propulsion synchronously, offering a mechanism to enact control over trajectories.